A method for preparing black polyimide film

By adding a decomposed monopoly ammonium salt during the synthesis of polybinamide film, and decomposing carbonization at high temperature, the existing black polytamine thin film has improved the performance of powder and dielectric performance during the processing process. High -performance and uniform black polytamide film.

CN116041701BActive Publication Date: 2025-01-28TAIHU HUAQIANG TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211601496.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-13
Publication Date
2025-01-28
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

The existing black polyimide films are prone to powder loss during subsequent processing, and the added black inorganic fillers are difficult to achieve molecular dispersion, resulting in increased dielectric constant and dielectric loss.

Method used

By adding ductulatanium salt during the synthesis process of polytamide glue, carbonization is used at high temperatures to achieve uniform blackization of the film, and the amine is completed when the aminoly temperature reaches 400-450 ℃. Available, improving mechanical properties and insulation performance.

Benefits of technology

The uniformity and high performance of the black polytamide film is achieved, avoiding the problem of powder loss, and maintaining a low and stable dielectric constant and dielectric loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116041701B_ABST
    Figure CN116041701B_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a black polyimide film, wherein a thermally decomposable quaternary ammonium salt compound is added to a synthesized polyamic acid solution; after the polyamic acid film to which the quaternary ammonium salt is added is subjected to high-temperature thermal imidization, the quaternary ammonium salt is thermally decomposed and carbonized inside the film to obtain carbon black micropowder that is well combined with polyimide molecules, thereby obtaining a black polyimide film. The prepared polyimide film is used as a covering film, and not only has good covering and insulating properties, but also does not have powder falling during later processing such as hole transfer and electroplating, greatly reducing the possibility of carbon black powder falling off and contaminating a circuit board, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyimide film for a flexible circuit board, in particular to a black polyimide film and a method for preparing the polyimide film. Background Art

[0002] With the rapid development of electronic products, mobile phones, tablets, car display devices and future wearable devices are all moving towards being short, thin and flexible. These new development directions have put forward higher requirements on the insulating materials used in electronic products.

[0003] Because traditional circuit boards are thick, hard and cannot be bent, they are no longer used in high-end electronic products. Instead, flexible circuit boards (FPCs) are used. The insulating materials in flexible circuit boards not only need to have good insulation and mechanical properties, but also need to have excellent processing properties. That is, during the subsequent processing of the flexible circuit board, the insulating material has excellent stability and continues to protect the circuit board. At the same time, as a covering film for the circuit board, many design manufacturers require it to cover the design ideas of the circuit board. In this case, black covering film came into being. The black design also makes the circuit board have a more high-end temperament, and is often used inside high-end mobile phones.

[0004] Polyimide film is the preferred insulating material for flexible copper clad laminate (FCCL) and is widely used because of its excellent mechanical properties, insulation properties, low dielectric constant and dielectric loss. The design of FCCL is a double-layer, three-layer or multi-layer design that alternately laminates a layer of copper foil and a layer of polyimide film. FPC is a combination and connection of FCCL. In order to achieve the patterning of the conductive layer and the mutual conduction between the multiple layers, subsequent processes such as etching, punching, electroplating, and oxidation are often required, which makes the polyimide film subject to chemical liquid corrosion, high temperature and other conditions to a certain extent, and the black covering film on the surface is no exception.

[0005] Many polyimide film manufacturers have been competing to apply for patents for black polyimide films, a large part of which is to change the color of the film by adding black inorganic fillers of different particle sizes during the polyimide glue making process, such as patent CN 102260408A, adding inorganic black pigments, such as: Co3O4, CoO, Ni3O5, etc.; for example, CN104742461A, by adding carbon black, titanium black and bone charcoal as black pigments. In addition, there are a large number of patents for adding carbon black and patents for carbon black surface treatment to protect the production and preparation technology of black polyimide covering films. However, the addition of black inorganic fillers, no matter how fine the particle size control is, cannot achieve true molecular-level dispersion, which causes the black covering film to fall off in the subsequent processing process, polluting production equipment and products, such as flexible circuit boards. Most importantly, since carbon black has a certain conductivity, if it is not properly selected, the dielectric constant and dielectric loss of the black polyimide film will increase. In addition, there are some patented polyimide resins that are synthesized to be inherently black, and the film itself is black, such as CN109180936A and CN 113072700A. However, the synthesis process requires special monomers, and the raw materials are not easy to obtain, resulting in high costs, and the covering power is not enough. Summary of the invention

[0006] In order to solve the above problems, the present invention aims at the demand for black polyimide and the technical difficulties. The polyimide is prepared by adding an easily decomposable quaternary ammonium salt in the synthesis process of the polyimide glue. The decomposition temperature of the quaternary ammonium salt is between 170-350°C. The quaternary ammonium salt is dispersed in the polyamic acid solution and the film at the molecular level. As the imidization temperature of the film gradually increases, the quaternary ammonium salt is decomposed and carbonized in the film, so that the film is transformed from brown to uniform black. Finally, the imidization temperature reaches 400-450°C, the film is completely imidized, and the mechanical properties and insulation properties are optimized.

[0007] First, in a first aspect of the present invention, a method for preparing a black polyimide film is provided, which comprises the following steps:

[0008] 1) The diamine monomer is dissolved in an organic solvent, and a certain amount of dianhydride monomer is added to carry out polymerization reaction to obtain polyimide;

[0009] 2) adding quaternary ammonium salt to dissolve;

[0010] 3) subjecting the polyimide and quaternary ammonium salt solution to film-forming treatment under heating conditions;

[0011] 4) Continue heating and keep heating to obtain a black polyimide film.

[0012] In a preferred embodiment, the organic solvent is a non-protonated polar solvent, which is a commonly used solvent for synthesizing polyimide. Preferably, the solvent is selected from one or more of the following: N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, etc.; preferably, the non-protonated polar solvent is selected from N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAc) and N,N-dimethylformamide (DMF).

[0013] In some embodiments, the quaternary ammonium salt is a type of quaternary ammonium salt stabilized by carboxylate groups. Preferably, the quaternary ammonium salt is selected from one or two of the following structures:

[0014]

[0015] Wherein, R1, R2, R3, R4 and R5 may be the same or different, and are independently selected from hydrocarbon groups, preferably alkyl groups, and more preferably C1 to C 16 In some technical solutions, the alkyl group is a branched alkyl group; even more preferably, the quaternary ammonium salt is selected from:

[0016] Quaternary ammonium salt 1: or

[0017] Quaternary ammonium salt II:

[0018] In some embodiments, the diamine monomer is a diamine monomer commonly used in synthesizing polyimide, for example, one or more selected from the following structures: m-phenylenediamine, p-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 2,2'-trifluoromethyl-4,4'-benzidine, 9,9-bis(4-aminophenyl)fluorene, 1,3-bis(4-aminophenoxy)benzene, the structure of which is as follows:

[0019]

[0020] In some embodiments, the dianhydride monomer is selected from dianhydride monomers commonly used in the synthesis of polyimide, for example, one or more selected from the following structures: pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 3,3',4,4'-diphenyl ether tetracarboxylic anhydride, 3,3',4,4'-benzophenone tetracarboxylic anhydride, or 4,4'-(hexafluoroisopropylene) diphthalic anhydride, whose structure is as follows:

[0021] In some embodiments, the reaction is carried out under nitrogen protection.

[0022] In some embodiments, the solid content of the diamine and dianhydride monomers is 10-50wt%, preferably 10-35wt%; the amount of the quaternary ammonium salt accounts for 1-30% of the total mass of the diamine and dianhydride monomers, preferably 5-25%; more preferably 10%-20%. The mass ratio of the non-protonated polar solvent to the diamine monomer is about 5-10:1, preferably 7-8:1.

[0023] In some embodiments, in step 1), the diamine monomer is completely dissolved by stirring; in the step of adding the dianhydride, it is slowly added in batches and gradually dissolved; and the polymerization reaction time is 5-20 hours, preferably 6-18 hours, and more preferably 6-15 hours.

[0024] In the step 2), the quaternary ammonium salt is fully dissolved and then mixed for reaction. Preferably, the reaction time is 2-5 hours, preferably 3 hours.

[0025] In the step 3), the polymerization reaction mixture is cast into a film, and the film is formed into a self-supporting PAA film at a temperature of 100-200° C., preferably 150-170° C.

[0026] In the step 4), the film is heated to 400-500° C., preferably 420-450° C. in an imide furnace, and maintained at this temperature for 1-15 min, preferably 2-10 min, more preferably 5-8 min, and cooled to obtain a black polyimide film.

[0027] In some embodiments, the method for preparing a black polyimide film comprises the following specific steps:

[0028] 1) In a synthesis reactor protected by nitrogen, a certain amount of diamine monomer is added, and then a sufficient amount of non-protonated polar solvent is added to completely dissolve the diamine; a dianhydride monomer equivalent to the diamine is added in batches, and the viscosity is observed to gradually increase, and the reaction is carried out under nitrogen protection for 6-24 hours;

[0029] 2) After the reaction is complete, add quaternary ammonium salt in an amount of 1-30% of the total mass of the diamine and dianhydride monomers and dissolve for 2-4 hours;

[0030] 3) After sufficient dissolution, the film is cast to obtain a self-supporting polyamic acid film at 150-170°C;

[0031] 4) The temperature in the imide furnace is then gradually raised from 200°C to between 400°C and 450°C, and the temperature is kept in the furnace for a sufficient time to complete the imidization and decomposition and carbonization of the quaternary ammonium salt, thereby obtaining a black polyimide film.

[0032] In another aspect of the present invention, the present invention relates to a polyamic acid solution for coating and forming a black polyimide film, wherein the solution mixture comprises:

[0033] 1) Diamine and dianhydride monomers;

[0034] 2) non-protonated polar solvents; and

[0035] 3) A quaternary ammonium salt; characterized in that

[0036] The quaternary ammonium salt of the specific structure refers to a type of quaternary ammonium salt stabilized by carboxylate groups. Preferably, the quaternary ammonium salt is selected from one or more of the following structures:

[0037]

[0038] Wherein, R1, R2, R3, R4 and R5 may be the same or different, and are independently selected from hydrocarbon groups, preferably alkyl groups, and more preferably C1 to C 16 In some technical solutions, the alkyl group is a branched alkyl group; even more preferably, the quaternary ammonium salt is selected from:

[0039] Quaternary ammonium salt 1: or

[0040] Quaternary ammonium salt II:

[0041] In some embodiments, the thermal decomposition temperature of the quaternary ammonium salt is between 170-350°C; preferably, the thermal decomposition temperature of the quaternary ammonium salt is between 200-350°C or between 170-300°C; more preferably, the thermal decomposition temperature of the quaternary ammonium salt is between 200-300°C.

[0042] In some embodiments, the diamine monomer is selected from the monomers commonly used for synthesizing polyimide, for example, one or more selected from the following structures: m-phenylenediamine, p-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 2,2'-trifluoromethyl-4,4'-benzidine, 9,9-bis(4-aminophenyl)fluorene, 1,3-bis(4-aminophenoxy)benzene, the structure of which is as follows:

[0043]

[0044] In some embodiments, the dianhydride structure is selected from one or more of the following structures: pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 3,3',4,4'-diphenyl ether tetracarboxylic anhydride, 3,3',4,4'-benzophenone tetracarboxylic anhydride, or 4,4'-(hexafluoroisopropylene) diphthalic anhydride, the structure of which is as follows:

[0045] In some embodiments, the diamine and dianhydride monomers are 10-50 wt%, preferably 10-35 wt%; the quaternary ammonium salt accounts for 1-30%, preferably 5-25% of the total weight of the diamine and dianhydride monomers.

[0046] In a preferred embodiment, the organic solvent is a non-protonated polar solvent, which is a commonly used solvent for synthesizing polyimide. Preferably, the solvent is selected from one or more of the following: N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, etc.; preferably, the non-protonated polar solvent is selected from N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAc) and N,N-dimethylformamide (DMF).

[0047] In another aspect of the present invention, it relates to a black polyimide film, which is obtained by the preparation method described above in the present invention. Specifically, the black polyimide film described in the present invention is prepared by the polyamic acid solution described above in the present invention.

[0048] Specifically, the polyamide solution can be cast at 150-170° C. to form a self-supporting polyamic acid film, and the imidization temperature is gradually increased from 200° C. to 400-450° C. to achieve imidization and decomposition and carbonization of the quaternary ammonium salt, thereby forming a black polyimide film.

[0049] Unless otherwise defined, the meanings of the terms used in the present invention are the same as those understood by those skilled in the art. The publications, patents / patent applications, or other references cited in the present invention are incorporated herein by reference in their entirety.

[0050] As used herein, the term "comprising" and its variations also include different and varied terms, such as but not limited to "consisting essentially of" or "consisting of." When necessary, the numerical ranges provided herein also include sub-ranges therebetween.

[0051] As used herein, unless otherwise defined, the terms "a" or "an" in the present invention are used to describe the elements, components, ingredients, steps or members; they should be understood to include one / one or at least one / one, and "plurality / multiples" means two / two or two / more than two.

[0052] Unless otherwise defined, all numerical ranges cited in the present invention include endpoint values. The numerical values ​​in the present invention are all approximate values. Regardless of whether "about" or "approximately" is used, the numerical values ​​of the present invention may differ by 1%-10%, and the range between the numerical value -10% and the numerical value +10% is also disclosed at the same time.

[0053] The black polyimide film prepared by the present invention has a simple process and is easy to implement, and can avoid powder loss during the later processing; and the black polyimide film prepared by the present invention can maintain a relatively low and stable dielectric constant and dielectric loss.

[0054] To clearly illustrate the technical solution of the embodiment of the present invention, the steps involved in the embodiment and the corresponding drawings are introduced and explained below. Obviously, the drawings or embodiments described below are only examples of a part of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 : Thermogravimetric curve of quaternary ammonium salt in Example 1;

[0056] Figure 2 : Electron microscope photo of the cross section of the film of Example 1;

[0057] Figure 3 : Electron microscope photo of the cross section of the film of Example 2;

[0058] Figure 4 : Electron microscope photo of the cross section of the film of Example 3;

[0059] Figure 5 : Electron microscope photo of the cross section of the film of comparative example 1;

[0060] Figure 6 : Electron microscope photograph of the cross section of the film of comparative example 2. DETAILED DESCRIPTION

[0061] The present invention will be better understood with reference to the above-mentioned drawings and the following examples. However, it should be understood that the drawings and examples of the present disclosure are only for illustrative purposes and represent only some specific embodiments of the present invention, and are not intended to limit the scope of protection of the present disclosure, which can be implemented in various forms. In the following examples, the coating film thickness is controlled to be 25um±2um.

[0062] Embodiment 1:

[0063] In a nitrogen-protected reactor, add 2kg (10mol) of 4,4'-diaminodiphenyl ether and 15kg of DMAc solvent, stir until completely dissolved, then slowly add 2.18kg (10mol) of pyromellitic anhydride in batches. As the dianhydride gradually dissolves, the viscosity of the solution gradually increases. After fully reacting for 6-8 hours, add 0.21kg (5wt%) of quaternary ammonium salt 1 and fully dissolve and mix for 2 hours. Cast film, at 150°C, it becomes a self-supporting PAA film, then enters the imide furnace and gradually heats from 200°C to 400°C, and maintains for 10 minutes. After cooling, a black polyimide film sample 1 is obtained for testing.

[0064] Embodiment 2:

[0065] In a nitrogen-protected reactor, add 0.54kg (5mol) of p-phenylenediamine, 1kg (5mol) of 4,4'-diaminodiphenyl ether and 14kg of DMF solvent, stir until completely dissolved, then slowly add 1.47kg (5mol) of 3,3',4,4'-biphenyltetracarboxylic anhydride and 1.09kg (5mol) of isophthalic anhydride in batches. As the anhydride gradually dissolves, the viscosity of the solution gradually increases. After fully reacting for 12-15 hours, add 0.41kg (10wt%) of quaternary ammonium salt 1, fully dissolve and mix for 3 hours. Cast film, at 150°C, become a self-supporting PAA film, then enter the imide furnace and gradually heat from 200°C to 420°C, and maintain for 6 minutes. After cooling, a black polyimide film sample 2 is obtained for testing.

[0066] Embodiment 3:

[0067] In a nitrogen-protected reactor, add 0.108kg (1mol) of p-phenylenediamine, 1.8kg (9mol) of 4,4'-diaminodiphenyl ether and 14kg of NMP solvent, stir until completely dissolved, then slowly add 0.588kg (2mol) of 3,3',4,4'-biphenyltetracarboxylic anhydride and 1.74kg (8mol) of isophthalic anhydride in batches. As the anhydride gradually dissolves, the viscosity of the solution gradually increases. After fully reacting for 12-15 hours, add 0.847kg (20wt%) of quaternary ammonium salt 1, fully dissolve and mix for 3 hours. Cast film, at 150°C, become a self-supporting PAA film, then enter the imide furnace and gradually heat from 200°C to 430°C, and maintain for 5 minutes. After cooling, a black polyimide film sample 3 is obtained for testing.

[0068] Embodiment 4:

[0069] In a nitrogen-protected reactor, add 0.348kg (1 mol) of 9,9-bis (4-aminophenyl) fluorene, 1.8kg (9 mol) of 4,4'-diaminodiphenyl ether and 18kg of DMAc solvent, stir until completely dissolved, and then slowly add 4.44kg (10 mol) of 4,4'-(hexafluoroisopropylene) diphthalic anhydride in batches. As the dianhydride gradually dissolves, the viscosity of the solution gradually increases. After fully reacting for 15-20 hours, add 1.65kg (25wt%) of quaternary ammonium salt II and fully dissolve and mix for 3 hours. Cast film, at 150°C, it becomes a self-supporting PAA film, and then enters the imide furnace and gradually heats from 200°C to 450°C, and maintains for 5 minutes. After cooling, a black polyimide film sample 4 is obtained for testing.

[0070] Embodiment 5:

[0071] In a nitrogen-protected reactor, add 2.92kg (10mol) of 1,3-bis (4-aminophenoxy) benzene and 16kg of DMAc solvent, stir until completely dissolved, then slowly add 2.18kg (10mol) of pyromellitic anhydride in batches. As the dianhydride gradually dissolves, the viscosity of the solution gradually increases. After fully reacting for 15-20 hours, add 0.765kg (15wt%) of quaternary ammonium salt II, fully dissolve and mix for 3 hours. Cast film, at 150°C, become a self-supporting PAA film, then enter the imide furnace and gradually heat up from 200°C to 450°C, and maintain for 2 minutes. After cooling, a black polyimide film sample 5 is obtained for testing.

[0072] Comparative Example 1:

[0073] In a nitrogen-protected reactor, add 2kg (10 mol) of 4,4'-diaminodiphenyl ether and 15kg of DMAc solvent, stir until completely dissolved, and then slowly add 2.18kg (10 mol) of pyromellitic anhydride in batches. As the dianhydride gradually dissolves, the viscosity of the solution gradually increases. After fully reacting for 6-8 hours, add 1.05kg of a carbon black dispersion containing 20wt% solids. The volume average diameter of the carbon black particles is 1-2um (D 90 =2.24um), fully mixed for 5 hours. Cast film, a self-supporting PAA film at 150°C, then enter the imide furnace and gradually heat up from 200°C to 450°C, and maintain for 2 minutes. After cooling, a black polyimide film sample 6 is obtained, to be tested.

[0074] Comparative Example 2:

[0075] In a nitrogen-protected reactor, 2 kg (10 mol) of 4,4'-diaminodiphenyl ether and 15 kg of DMAc solvent were added. After stirring until completely dissolved, 2.18 kg (10 mol) of pyromellitic anhydride was slowly added in batches. As the dianhydride gradually dissolved, the viscosity of the solution gradually increased. After fully reacting for 6-8 hours, 1.05 kg of a carbon black dispersion containing 20 wt% solids was added. The volume average diameter of the carbon black particles was less than 1 μm (D 90 =1.81um), fully mixed for 5 hours. Cast film, at 150℃ to become a self-supporting PAA film, then enter the imide furnace and gradually heat up from 200℃ to 400℃, and maintain for 10 minutes. After cooling, a black polyimide film sample 7 is obtained, to be tested.

[0076] Performance evaluation:

[0077] Test Method :

[0078] 1. Thermogravimetric analysis (TGA): Mettler-Toledo TGA1 thermogravimetric analyzer;

[0079] 2. Scanning electron microscope (SEM): CARL ZEISS ULTRA 55 field emission scanning electron microscope, surface gold spraying test;

[0080] 3. Transmittance (%): The transmittance of 25 μm film at 450 nm was measured using a UV-1601 SHIMADZU UV-visible spectrometer from Japan;

[0081] 4. 60° glossiness: German BYK Chemical AG-4448;

[0082] 5. Dielectric constant (Dk) and dielectric loss (Df): Alpha-A, Novocontrol, Germany, test frequency 1MHz.

[0083] Test Results :

[0084] The test results of transmittance, 60° glossiness, dielectric constant and dielectric loss of the black polyimide samples in Examples 1-5 and Comparative Examples 1 and 2 are shown in Table 1 below.

[0085] Table 1: Test results of samples obtained from the embodiments and comparative examples

[0086]

[0087]

[0088] The distribution of microparticles obtained by carbonization of quaternary ammonium salt in the film was observed by testing the electron microscope photos of the film cross section. It can be found that the black polyimide film ( Figure 2-Figure 4 ), the carbon black size is uniform and fine, and it is evenly dispersed. However, in the black film prepared by adding black color pastes of different sizes, the carbon black inside has been agglomerated, the granularity is obvious, and it is not easy to disperse evenly, thus affecting subsequent processing.

[0089] The above description is only an example of the implementation of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A method for preparing a black polyimide film, comprising the following steps: 1) dissolving a diamine monomer in an organic solvent, adding a dianhydride monomer to carry out polymerization to obtain a polyimide; 2) adding quaternary ammonium salt to dissolve; 3) subjecting the polyimide and quaternary ammonium salt solution to film-forming treatment under heating conditions; 4) Continue heating and stop to obtain a black polyimide film; in, The structure of the quaternary ammonium salt is: Wherein, R1, R2, and R3 may be the same or different and are independently selected from alkyl groups.

2. The method of claim 1, wherein: The alkyl group is C1~C 16 of alkyl.

3. The method of claim 1, wherein: The quaternary ammonium salt is selected from: Quaternary ammonium salt 1: Quaternary ammonium salt II:

4. The method of claim 1, wherein the diamine monomer is selected from one or more of the following structures:

5. The method of claim 1, wherein the dianhydride monomer is selected from one or more of the following structures: The method of claim 1 , wherein the organic solvent is a non-protonated polar solvent.

7. The method of claim 6, wherein the non-protonated polar solvent is selected from one or more of the following: N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile.

8. The method according to any one of claims 1 to 7, wherein the reaction is carried out under nitrogen protection.

9. The method according to any one of claims 1 to 7, wherein the solid content of the diamine and dianhydride monomers is 10-50wt%; and the amount of the quaternary ammonium salt accounts for 1-30% of the total mass of the diamine and dianhydride monomers.

10. The method of claim 9, wherein the diamine and dianhydride monomers have a solid content of 10-35 wt%.

11. The method of claim 9, wherein the quaternary ammonium salt is used in an amount of 5-25% of the total mass of the diamine and dianhydride monomers.

12. The method of claim 9, wherein the quaternary ammonium salt is used in an amount of 10% to 20% of the total mass of the diamine and dianhydride monomers.

13. The method according to any one of claims 1 to 7, wherein: In the step 3), the reactant is cast into a self-supporting polyimide film at a temperature of 100-200°C.

14. The method of claim 13, wherein: In the step 3), the reactant is cast into a self-supporting polyimide film at a temperature of 150-170°C.

15. The method according to claim 13, wherein in step 4), the film is heated to 400-500°C in an imide furnace and maintained at this temperature for 1-15 minutes, and then cooled to obtain a black polyimide film.

16. The method according to claim 13, wherein in step 4), the film is heated to 420-450°C in an imide furnace and maintained at this temperature for 1-15 minutes, and then cooled to obtain a black polyimide film.

17. A black polyimide film, characterized in that: It is prepared according to any one of claims 1-16.

18. A polyamic acid solution for coating and forming a black polyimide film, wherein the solution comprises: 1) Diamine and dianhydride monomers; 2) non-protonated polar solvents; and 3) A quaternary ammonium salt; characterized in that The structure of the quaternary ammonium salt is: Wherein, R1, R2, and R3 are independently selected from alkyl groups; the thermal decomposition temperature of the quaternary ammonium salt is between 170-350°C; Wherein, the diamine monomer is selected from one or more of the following structures: The dianhydride structure is selected from one or more of the following structures: The non-protonated polar solvent is selected from one or more of the following: N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and acetonitrile.

19. The solution of claim 18, wherein the alkyl group is C1 to C 16 of alkyl.

20. The solution of claim 18, wherein the quaternary ammonium salt is selected from: Quaternary ammonium salt 1: Quaternary ammonium salt II:

Citation Information

Patent Citations

  • Black polyimide film and copper foil laminate containing the film

    CN102260408A

  • Low-glossiness dual-layer polyimide film and manufacturing method thereof

    CN104742461A

  • Intrinsic black polyimide film, and preparation method and applications thereof

    CN109180936A

  • Intrinsic black polyimide film with improved mechanical properties and preparation method thereof

    CN113072700A

  • Waterproof transparent polyimide film, preparation method and application thereof

    CN113174072A